Aspek loneliness tokoh utama dalam roman "Die Verwandlung" karya Franz Kafka: Analisis Psikologi Sastra - Amalinda, Syifa Rizki; Setiawan, Akbar Kuntardi (Journal of Culture, Literature and Foreign Language Teaching, 2025)
This research aims to describe the forms of loneliness aspects experienced by the main character in the romance Die Verwandlung by Franz Kafka using literary psychology studies. This research uses a psychological approach by utilizing Bruno's theory of loneliness. The research data collected in the form of quotations of words, phrases, sentences, and paragraphs that describe aspects of loneliness based on Bruno's theory, experienced by the main character in the romance Die Verwandlung. The data source in this research is obtained from the romance Die Verwandlung by Franz Kafka. The research instrument in this research is human instrument or the researcher himself. Data collection techniques used reading and note-taking techniques. The data were analyzed using descriptive qualitative technique, which describes the aspects of loneliness that occur in the main character. The validity of the data in this study was obtained by using semantic validity. The results showed that:  There are 46 data divided into 7 aspects of loneliness experienced by Gregor Samsa in the romance Die Verwandlung, including 1) Isolation, 2) Rejection, 3) Feeling not understood, 4) Feeling unloved, 5) Having no friends, 6) Feeling bored, and 7) Restlessness. Of the seven aspects of loneliness, feelings of isolation, rejection and feeling unloved are the most common aspects found in this study, totaling 11 data from each of these aspects.